Identifikasi Serangga Ordo Lepidoptera pada Ekosistem Sayuran di Desa Ogan Ilir - Keshya, Aaliyah; Yeni, Belia; Rachmatika, Devita; Rahmawati, Lusi; Andika, Rafi; Arrahsal, Uwais; Umayah, Abu; Gunawan, Bambang; Arsi, Arsi (Seminar Nasional Lahan Suboptimal, 2022)
Keshya A, Yeni B, Rachmatika D, Rahmawati L, Andika R, Arrahsal U, Umayah A, Gunawan B, Arsi A. 2022. Identification of insects of the order lepidoptera in vegetable ecosystems in Ogan Ilir Village. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang  27 Oktober 2022. pp. 635-640. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Identification of insects of the order Lepidoptera on vegetable crops in the village of Ogan Ilir. From the many orders of the Arthropoda group, there are many groups of insects whose role is very important in increasing plant productivity, namely the Order Lepidoptera. Butterflies can be used as indicators of environmental change because they are vulnerable to disturbances around them. The purpose of this study was to find information about species of the order Lepidoptera found in Ogan Ilir Regency. Observations were made on vegetable plantations in the village of ogan ilir. The research method uses field observation methods with insect and roaming network techniques. From the results of the identification of butterfly species carried out around the area of Ogan ilir Regency, it showed that the total number of butterfly species found were 10 species belonging to the families Erebidae, Zygaenidae, Lycaenidae, Nymphalidae. This study provides information about the types of species of the order Lepidoptera that can be used as an indicator of the sustainability of an ecosystem in Ogan Ilir Regency. Thus, it is necessary to improve the quality of an ecosystem that affects the population of the order Lepidotera as an indicator that makes ecosystem sustainability.